Three-dimensional tracking of coronary arteries from biplane angiographic sequences using parametrically deformable models. - Sarry, L. (IEEE Transactions on medical imaging)
A new method for coronary artery tracking in biplane digital subtraction is presented. The dynamic tracking of nonrigid objects from two views is achieved using a generalization of parametrically deformable models. Three-dimensional (3-D) Fourier descriptors used for shape representation are obtained from the two-dimensional (2-D) descriptors of the projections. A new constraint inferred from epipolar geometry is applied to the contour model. Direct 3-D tracking is compared with the classical approach in two steps: independent 2-D tracking in each of the two projection planes; 3-D reconstruction using the epipolar constraint. Convergence quality and accuracy of the 3-D reconstruction are analyzed for several sequences showing different displacement amplitudes, deformation rates and image contrasts.